OP19 Management of spontaneous bacterial peritonitis at York and Scarborough Teaching Hospitals NHS Foundation Trust (YSTHFT). Are we getting it correct, and on time?. (20th September 2022) - Pratt, Anthony; Ong, Melissa; Driver, Robert; Arikichenin, Oli; Gott, Naomi; Orange, Dawn; Millson, Charles
Abstract : Spontaneous Bacterial Peritonitis (SBP) is the infection of the ascitic fluid without any surgically treatable source of infection. SBP is diagnosed when an ascitic sample contains >250 neutrophils/mm 3 . The laboratory at YSTHNHSFT report ascitic white cell counts (WCC) instead with a percentage of polymorphs, allowing a neutrophil count to be estimated. Management of SBP includes empirical antibiotic therapy as soon as possible and albumin in select patients at risk of renal impairment. The Improving Quality in Liver Services (IQILS) programme requires liver services to audit antibiotics and albumin prescriptions within 12 hours of SBP diagnosis. Secondary prophylactic antibiotics are also recommended to prevent further episodes. Retrospective data for all patients at YSTHFT who underwent an ascitic tap in 2021 were identified from the laboratory information system. Electronic patient records and prescriptions were examined to determine the relevance of an ascitic WCC >250/mm 3, if any subsequent antibiotics were prescribed and any albumin requested from the transfusion department. From a total of 361 ascitic tap samples, 55 were found to have a WCC of >250/mm 3 but only 24 were thought to be cirrhosis related SBP. All 24 patients were prescribed antibiotics but only 21/24 (87.5%) were prescribed within 12 hours. 12/24 (50%) patients were prescribed subsequent secondary antibiotic prophylaxis while 7/24 (29.2%) were discharged from hospital without. The remaining 5/24 (20.8%) died before prophylaxis could be initiated. Albumin was requested within 12 hours of diagnosis for 10/24 (41.7%) patients and after 12 hours in 7/24 (29.2%). 7/24 (29.2%) received no albumin. 7/24 (29.2%) had an acute kidney injury (AKI) at diagnosis and 1/24 (4.2%) developed an AKI after not receiving the correct dose of albumin. Those that did receive albumin received various amounts with only 4/24 (16.7%) receiving the recommended dose of 1.5 g/kg on day 1 and 1 g/kg on day 3. All patients were prescribed treatment antibiotics for SBP, mostly within 12 hours of diagnosis. Implementation of an electronic prescribing order set aims to prompt prescribers to consider secondary prophylactic antibiotics for all patients. Albumin prescribing was inconsistent but can be standardised by reviewing our Trust SBP guideline in conjunction with the prescribing order set and encouraging the use of these among hepatology and gastroenterology colleagues.